Effects of Added Potassium to Diets with High or and Low Crystalline Lysine on Finishing Pig Growth Performance - Rafe Q. Royall; Robert D. Goodband; Mike D. Tokach; Joel M. DeRouchey; Jason C. Woodworth; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2022)
This experiment was conducted to evaluate the effect of balancing dietary cation-anion difference (DCAD) levels, via added potassium bicarbonate (KHCO3), to diets containing low or high levels of L-Lys HCL on growth performance of growing-finishing pigs. A total of 1,944 pigs (PIC L337 × 1050; initially 77.6 ± 1.88 lb BW) were used in a 120-d study to determine the effect of added potassium bicarbonate to diets containing low or high levels of crystalline lysine on growth performance and carcass characteristics of finishing pigs. Pens of pigs were blocked by BW and randomly allotted to 1 of 4 dietary treatments in a randomized complete block design arranged in a 2 × 2 factorial with main effects of KHCO3(0 vs. 0.4%), and L-Lys HCl level (low vs. high). There were 27 pigs per pen and 18 replicates per treatment and a similar number of barrows and gilts placed in each pen. Treatment diets were corn-soybean meal-based and formulated in four dietary phases (approximately 80 to 130 lb, 130 to 185 lb, 185 to 230 lb, and 230 to 285 lb). Dietary treatments were formulated such that in each phase the diet containing a low level of L-Lys HCl without KHCO3and the diet containing a high level of L-Lys HCl with KHCO3, had similar calculated DCAD values. Additionally, the diet with a low level of L-Lys HCl with KHCO3was formulated to have the highest DCAD in each phase, while the diet with a high level of L-Lys HCl without KHCO3was formulated to have the lowest DCAD. Overall, there was no evidence (P>0.10) for a KHCO3× L-Lys HCl interaction or main effect for final BW or any observed growth response or carcass characteristics. The results of this study suggest that supplementing KHCO3to finishing pig diets with either high or low levels of L-Lys HCl and the corresponding changes in DCAD values did not impact growth performance or carcass characteristics.
Keywords: crystalline lysine; dietary cation-anion difference; finishing pig; potassium